The Role and Significance of Dental Development Atlas in Age Estimation - Karadayı, Beytullah; Afşin, Hüseyin; Karadayı, Şükriye; Özaslan, Abdi (The Bulletin of Legal Medicine, 2014)
Atlases visualizing the development and eruption of teeth are used for age estimation in dentistry practices and in forensic sciences. Since this method can be used both for living people and for corpses and is very practical, it provides a big advantage. It is especially practical and effective in identification studies during disasters with many victims. This study is a validation study of a tooth development atlas created for juvenile citizens of the Turkish Republic. 80 panoramic teeth graphs of 5-22-year-old individuals whose age and sex is known were obtained from an imaging center within ethical principles under the condition that their personal information is kept confidential. The eruption and development phases of the teeth in each graph were assessed using the atlas method to estimate the age. It was found that age estimation for all graphs at and below 14 years-of-agewas made with 95% accuracy with ± 1 error margin and for the ones between 14-22 years-of-age was made with 92.5% accuracy with ± 2 error margin from the data of juvenile citizens of the Turkish Republic. It is understood that the tooth development atlas created by …….. et al. is useful and practical for forensic age estimation and identification studies of victims of mass disasters. Keywords: Dental age estimation, Dental development atlas, Panoramic graph, Turkish population.